Communication with paediatric patients in an intensive care unit - María Victoria Bellido Estévez; Adoración Carretero García; María José Espíldora González (Universidad de Alicante, 2012)
Communication between family, hospital personnel and paediatric patients with assisted ventilation (AVPP) presents severe difficulties for their extreme dependency, and their impaired physical condition to produce speech. These type of difficulties are always important to cope with and situations are made worse should the individual be a paediatric patient or an immigrant because of his language difficulties. Our aims were to identify either verbal and non verbal expressions used by the AVPP in a paediatric intensive care unit (ICU) to communicate with hospital staff and also with their family, and to design especial patterns, tables of images or pictures to express concepts, feelings or even questions to solve their basic needs, in Spanish, English, French or Arabic language. A retrospective study in four children (aged 1-14) diagnosed of congenital degenerative metabolic disease in an ICU was done. A three-year follow up was performed. A close and strict patients' observation by family as well as by hospital staff personnel, were recorded to determine not only face and eyes expressions when trying to communicate with other people but also body language. A 15 items questionnaire was presented to those hospital staff personnel with their own personal experiences with AVPP patients. Most frequently the type of gestures made by these patients is very common, very specific and its identification and knowledge by the sanitary professionals contributes to improve the quality of health care. The means for improving these sort of communication with AVPP patients provides ways to better cope with their needs and helps hospital personnel with less experience to widen their knowledge. Nurse professionals demand better and more advanced education courses in English, French, Arabic languages to improve their communication ability with foreign patients in order to obtain better health care assistance.